CEO Characteristics and Company Values: Can Board Gender Diversity Create Value? - Joubert Barens Maramis; Ivonne S. Saerang; Jessy DL Warongan (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2026)
This study examines the impact of CEO characteristics and board gender diversity on company value in Indonesia. The objective of this research is to analyze whether characteristics related to directors and commissioners influence firm value when measured using different financial proxies. This study applies a quantitative method using secondary data collected from companies in Indonesia. The analysis uses two different proxies for company value, namely the Market-to-Book Ratio and Tobin’s Q. The findings show that the gender variable of the president director is the only variable that significantly affects company value when measured using the Market-to-Book Ratio. However, when Tobin’s Q is used, four variables become significant, namely the total number of directors, female directors, commissioner age, and commissioner gender represented by the president commissioner. These findings indicate that the use of different proxies may produce different research results and interpretations regarding company value. Therefore, this study suggests that future research should consider multiple measurement proxies to obtain more comprehensive findings regarding corporate governance and firm value.